EVALUATION OF THE EFFECTS OF LAND COVER CHANGES AND URBANIZATION ON LAND SURFACE TEMPERATURE: A REMOTE SENSING STUDY OF SUB-WATERSHED OF OUED FEKAN, NORTHWEST ALGERIA - Chrair, Mohammed; Khaldi, A.; Hamadouche, M. A.; Hamimed, A.; Cernesson, Flavie; Alkan, Mehmet (YILDIZ TECHNICAL UNIV, 2020)
Urban growth is a worldwide phenomenon. The rate of urbanisation in developing countries such as Algeria is speedy. Sub-watershed of Oued Fekan is included in the large watershed of Macta which is located in northwestern Algeria and is one of the most important sites of this country characterized by an abundant amount of biodiversity as well as a highly productive ecosystem. The valuable landscape undergoes a radical change in the form of a sub-watershed recently due to anthropogenic change on land use and land cover. The exponential increase in population and human activities are increasing the demand for land and soil resources for agriculture, urban and industrial uses. Anthropogenic factors, especially urban sprawl, have a significant role in controlling the temperature change. In this paper, four Landsat-8 OLI/TIRS images of 2018 have been used from different seasons to estimate land surface temperature (LST), Normalized Difference Built-up Index (NDBI) and Normalized Difference Vegetation Index (NDVI) in order to study the phenomenon of difference distribution temperature in urban with the surrounding rural areas. Analysis based on linear regression was used to generate relationships between LST with NDVI and NDBI. Our analysis indicates that for the four seasons, a strong linear relationship between NDBI and LST was marked compared with the relationship between NDVI and LST, which was less intense and varied by seasons. We suggest that NDBI is a visible indicator for studying surface Urban Heat Island phenomenon (UHI). Useful information that occurs as a consequence of land-use changes and urbanization are then provided for understanding the local climate and environmental changes of our study area.
Keywords: Land surface temperature; urban heat Island; climate change; urbanization; landsat; Algeria; URBAN HEAT-ISLAND; ATMOSPHERIC CORRECTION; HOUSTON; GROWTH; INDEX; CITY; Engineering